2008
DOI: 10.1002/mde.1447
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and firm efficiency: evidence from China's publicly listed firms

Abstract: This paper applies a two-stage, double bootstrapping data envelope analysis approach to investigate whether and to what extent various distinctive corporate governance practices affect productive efficiency in a sample of 461 publicly listed manufacturing firms in China between 1999 and 2002. We find that firm efficiency is negatively related to state ownership while positively related to public and employee share ownership. In addition, the relationship between ownership concentration and firm efficiency is U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 53 publications
1
49
0
2
Order By: Relevance
“…Liu and Lu (2007) report a non-linear relationship between the largest shareholder's holdings and firms' management activities among Chinese listed firms. Lin et al (2009) report a similar result of a U-shaped relationship between the shareholding of the largest shareholder and firm efficiency. Further, Tian and Estrin (2008) find a U-shaped relationship between government ownership and firms' corporate value as measured by Tobin's Q and return on assets (ROA).…”
Section: Ownership Concentrationsupporting
confidence: 68%
See 2 more Smart Citations
“…Liu and Lu (2007) report a non-linear relationship between the largest shareholder's holdings and firms' management activities among Chinese listed firms. Lin et al (2009) report a similar result of a U-shaped relationship between the shareholding of the largest shareholder and firm efficiency. Further, Tian and Estrin (2008) find a U-shaped relationship between government ownership and firms' corporate value as measured by Tobin's Q and return on assets (ROA).…”
Section: Ownership Concentrationsupporting
confidence: 68%
“…Firth et al (2007) provide evidence that the larger and more active supervisory boards help to raise the quality of accounting information. However, Lin et al (2009) suggest that the supervisory committee is more decorative than functional since the board of supervisors has not been given the right to vote on executive decisions and the right to electing directors, managers, and financial officers. Chen et al (2009) find that supervisory boards cannot contribute significantly to firm efficiency.…”
Section: Board Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…They follow those of Cotter et al (1997) who concluded that the increase in shareholder dividends is conditioned by the strong presence of independent directors. Lin et al (2009) came to similar conclusions when they pointed out that corporate governance through its mechanisms intervene to neutralize the agency costs , protect the interests of all stakeholders, allow shareholders to increase their return on investment and achieve high performance.…”
Section: Analysis Of the Links Between The Composition Of The Board Amentioning
confidence: 86%
“…Lin et al (2009) similarly note that companies governance through its mechanisms intervenes to neutralize the agency costs, to protect the interests of all stakeholders, allow shareholders to increase their return on investment and therefore to achieve high performance. Moreover, Schiehll and Bellavance (2009) argue that independent directors better promote value creation within companies unlike interns.…”
Section: The Board Of Directorsmentioning
confidence: 99%